The frequency of occurrence of various variants of the structure of root canals and methods of their mechanical treatment in the practice of a dentist-therapist - T. L. Redinova; E. I. Pudova; I. Сh. Sharifullina; A. A. Yesyunina; I. V. Zagrebin (Эндодонтия Today, 2022)
Aim. Evaluation of the frequency of occurrence of various variants of the structure of root canals and methods for their processing in the practice of a dentist-therapist.Material and methods. 30 doctors who worked in the specialty "therapeutic dentistry" for 2-20 years were interviewed using questionnaires in various dental institutions in Izhevsk and Sarapul in the Udmurt Republic; and also analyzed 81 medical record of patients who underwent primary endodontic treatment for caries complication at LLC Center for Professional Dentistry "APEX" in Izhevsk for 6 months of 2022. The following data were copied from medical records: the age of the patient, the disease of the tooth, the number of diagnosed root canals and the method of their instrumental processing, as well as the size of the primary and main files. In a laboratory experiment, 30 human one-two-rooted teeth were used removed for orthodontic indications or for periodontal diseases in various techniques, and apical patency was assessed by irrigating the canals with a tinted solution to control its exit beyond the apex.Results. From the personal data, it was found that the second molars have the largest number of options for the number of root canals (from 1 to 5 root canals). In 73.4% of physicians, molars and lower incisors cause difficulty in instrumentation, in almost 75% of cases root canals are passable for files of size 10, when working with rotary instruments, preference is given to the Step Back method in the “one length” technique, the use of such instruments in such technique in 46.6% of cases leads to an increase in apical patency.